What Prevents More Small Firms from Using Professional Business Services? An Information and Quality-Rating Experiment in Nigeria - Anderson, Stephen J.; McKenzie, David (World Bank, Washington, DC, 2021)
Why do more small firms in developing countries not use the market for professional business services like accounting, marketing, and human resource specialists? Two key reasons may be that firms lack information about the availability of these services, and that they struggle to distinguish the quality of good versus bad providers. A brand recognition exercise finds that most small firms are unaware of most providers in this market, and a survey of service providers reveals that they largely rely on word-of-mouth and informal reputation mechanisms for acquiring customers. This study set up a business services marketplace that contains information about the different providers present in the market and used mystery shopper visits to develop a quality ratings system. A randomized experiment with more than 1,000 firms provided access to this marketplace to the treatment group and randomized whether firms received just information or also quality ratings. The provision of quality ratings information shifts small firms’ preferences over which provider they would like to use, increasing the average quality rating of their preferred providers by 0.2 to 0.4 ratings points out of 5. However, neither the provision of information nor these quality ratings had any significant impact on the likelihood that small firms go on to hire a business service provider over the subsequent six months. The results suggest that alleviating information frictions alone is insufficient to increase usage of professional business services.